การออกแบบอย่างเหมาะสมที่สุดสำหรับโครงสร้างเหล็กในระนาบโดยวิธีฮิวริสติก - สุนิสสา ทองศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The research presents the study and development of an optimum design for planar steel trusses with linear analysis and rigid frames with geometric nonlinear analysis by the heuristic method. Primary buckling and local buckling of members are considered in the design. The design criteria followed the AISC 2005 specifications using both the Allowable Strength Design (ASD) and the Load and Resistance Design (LRFD) Method. The proposed algorithm will select a possible minimum volume of the given plane steel structure and at the same time can safely carry all given loads. The study found that the heuristic method can b effectively applied to obtain an optimum design for planar steel trusses and rigid frames. In the algorithm, the final result will be the minimum value among 3 solutions from 25 calculations. Solution of each calculation, on the other hand, is either the one having value repeated itself three times or the minimum value from the solutions obtained after 300 iterations. Results from the selected steel structures compared to those studied by past researchers show that the proposed method yields 2.58 percent less volume for the truss. For other two samples of steel portal frames the method gives 3.73 and 16.38 percent less volume, respectively.